Mapa Mundi - Morales, José Pilar (1860)
Map shows major cities for six continents and coastline of "Oceano Glacial del Sur" [Antarctica]; angled perspective of the world from the polar regions; mountain ranges and peaks [worldwide] in profile. Includes boundary line for Oceania. Inset: Division del Globo en relacion de los continentes y los mares [Division of the globe in relation to the continents and seas] and Perfiles de las mayores alturas de la Tierra [Profiles of the highest peaks on Earth]. Relief shown by hachures and by profile. Scale [1:116.000.000].